Experiences of end of life care of patient's with motor neuron disease on non invasive ventilation. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Steel, Kimberley; Hodgson, Aruna; Waterman, David; Harrison, Sophie; Bentley, Andrew
Abstract : Background: In July 2010 NICE developed guidance on the use of non-invasive ventilation (NIV) in patients with Motor Neuron Disease (MND). In the North West of England the University Hospital of South Manchester (UHSM) provides a tertiary Long Term Ventilation Service (LTVS) which establishes NIV for patients in the region. The NICE guidance means increasing numbers of MND patients are being commenced on NIV and subsequently the number of patients reaching the end of their life on NIV is increasing. Method: As part of the service review UHSM LTVS carried out a postal survey of GP's whose patient's died between July 2010 and December 2010 to evaluate the end of life care of MND patients on NIV. Results: 12 GP's were contacted and 8 returned feedback. Place of death: 5 at home 2 in hospital 1 in a hospice There were multiple professionals involved in the patients' deaths; 5/8 of the patients had 3 or more professional disciplines involved. 5/8 patients had an Advance Decision to Refuse Treatment (ADRT); 3/5 related to the patient's ventilation – 2 relating to withdrawal and 1 stating a wish to die on NIV 5/8 patients died on NIV (including 2 with an ADRT for NIV withdrawal) GP's confidence in dealing with NIV was variable. Conclusion: There is increasing number of MND patients reaching the end of their lives dependent on NIV. The confidence of GP's is variable and the number of healthcare professionals involved with these patients is substantial. Although the majority of patients had ADRTs, these did not always relate to NIV. Even if it did, NIV was still continued. In light of these findings UHSM LTVS has recognised the need to develop multi-disciplinary 'end of life care' guidelines for patients with MND who are using NIV.